Self-regulation and tendency of smartphone addiction among college students - Wibowo, Muhammad Ridho Sukmo; Wahidah, Fatin Rohmah Nur; Agil, Hilda Meriyandah (Jurnal Ilmiah Psikologi Terapan, 2024)
Nowadays, students have become inseparable from smartphones. A smartphone’s purpose should primarily be to serve as an educational tool. However, it is discovered that its primary application is for social media, which can lead to addiction to smartphones. Effective self-regulation can serve as a firm foundation for individuals to utilize a smartphone in a disciplined and appropriate manner. This study aimed to empirically investigate the impact of self-regulation on the propensity of students to develop smartphone addiction. This study employed a quantitative methodology, namely simple linear regression analysis. The sampling technique employed was purposive sampling, with a total sample size of 155 students. The measurement method used a smartphone addiction tendency scale (α = 0.849) and a self-regulation scale (α = 0.861). The findings of this study indicate that self-regulation has a significant impact on the propensity to develop smartphone addiction (β = -0.263; p<0.05). As a result, self regulation has the potential to mitigate the inclination towards smartphone addiction. The provided funding can be utilized as empirical evidence for assessing the impact of self-regulation on the susceptibility to smartphone addiction.